Determination of Metoprolol in Pharmaceutical Preparations by Zero, First, Second and Third Order Derivative Spectrophotometric Method - B. YILMAZ (International Journal of Pharma and Bio Sciences, 2010)
In this study, zero-, first-, second- and third-order derivative spectrophotometry methods were developed for the determination of metoprolol in pharmaceutical preparations. In zero order spectrophotometry, absorbance values were measured at 276 nm in zero order spectra of solution of metoprolol in methanol in the range of 240-310 nm. In first derivative spectrophotometry, absorbance values were measured at 265, 278 and 285 nm. In second derivative spectrophotometry, absorbance values were measured at 276, 279, 287 and 282 nm. In third derivative spectrophotometry, absorbance values were measured at 275, 278 and 281 nm. Parameters such as linearity, precision, accuracy, specificity, stability, limit of detection and limit of quantitation were studied according to the International Conference on Harmonization Guidelines. All the methods developed were successfully applied to two tablet formulation and the results were compared statistically with each other.